Resilience thinking: a renewed system approach for sustainability science - Xu, L.; Marinova, Dora; Guo, X. (Springer-Verlag Tokyo, 2014)
This paper examines the contribution of resilience thinking for social-ecological systems (SESs) in understanding sustainability and the need to preserve natural resources in the face of external perturbations. Through qualitative and quantitative analysis, the literature survey shows the increased importance of resilience and its integration into the interdisciplinary area of sustainability studies. By exploring the links between resilience and sustainability, the analysis finds that these two concepts share some similarities and also highlight the differences. The discussion of resilience indicators, measuring criteria, models and management issues reveals how resilience contributes to sustainability science and in what ways the concept can be used to measure resilience in terms of sustainability. Most existing studies emphasise the ecological aspects of resilience, but only by including human activities in the modelling can resilience thinking inform sustainability in a meaningful way. The paper concludes defining issues requiring further investigation, such as identifying and managing the drivers and key elements of resilience in SESs, exploring the dynamics between critical variables of SESs and the system feedbacks to external perturbations, as well as evaluating policies and engaging stakeholders for building resilience.